Antibacterial and anti-trichomunas characteristics of local landraces of Lawsonia inermis L. - M. Fatahi Bafghi; S. Salary; F. Mirzaei; H. Mahmoodian; H. Meftahizade; R. Zareshahi (BMC, 2022)
Abstract Background Henna (Lawsonia inermis) with anti-bacterial properties has been widely used in traditional medicine especially Persian medicine. Henna oil is suggested for diseases of infectious origin, such as cervical ulcers. Group B Streptococcus agalactiae, Pseudomonas aeruginosa and, Trichomonas vaginalis are involved in the infection of women especially cervicitis. Henna grows in dry and tropical regions. The main important landraces of henna landraces are cultivated in Kerman, Sistan and Baluchestan, Hormozgan, and Bushehr provinces in Iran. Proper use of antimicrobial agents, use of new antimicrobial strategies, and alternative methods, such as herbal methods may help reduce drug resistance in the future. This study's objective was to investigate the anti-Trichomonas vaginalis activity of three different henna landraces and antimicrobial effects against group B Streptococcus agalactiae and, Pseudomonas aeruginosa. Methods Total phenol content was measured by Folin ciocaltu method. Antibacterial effect of landraces of Henna against P. aeruginosa and S. agalactiae were assayed by well diffusion method and minimal inhibitory concentration assessments were done using the broth micro-dilution technique. Anti-Trichomonas effect of Henna landraces were assayed by Hemocytometery method. Results Total phenol content of Shahdad, Rudbar-e-Jonub, and Qaleh Ganj was 206.51, 201.96, and 254.85 μg/ml, respectively. Shahdad, Rudbar-e-Jonub, and Qaleh Ganj had MIC against GBS at 15, 15 and, 4 μg/ml. The growth inhibition diameter of the most effective henna (Shahdad landrace) at a concentration of 20 μg/ml on P. aeruginosa was 2.46 ± 0.15 cm and in the MIC method at a concentration of 5 μg/ml of Shahdad landrace, P. aeruginosa did not grow. IC50 of shahdad Henna after 24 h, 48 h, and 72 h was 7.54, 4.83 and 20.54 μg/ml, respectively. IC50 of Rudbar-e-Jonub extract was 5.76, 3.79 and 5.77 μg/ml in different days. IC50 of Qaleh Ganj extract was 6.09, 4.08 and 5.74 μg/ml in different days. Conclusions The amount of total phenol in Qaleh Ganj was higher than the other varieties. In the well diffusion method, Qaleh Ganj was more effective against group B Streptococcus (Gram-positive bacterium) than the other two landraces, and Shahdad landrace was more effective against P. aeruginosa (Gram-negative bacterium) than other. In the MIC method, the same result was obtained as in the well diffusion method, but at a lower concentration.